2024
DOI: 10.1099/jmm.0.001790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and public health implications of increasing notifications of LEE-negative Shiga toxin-producing Escherichia coli in England, 2014–2022

Ella V. Rodwell,
David R. Greig,
Gauri Godbole
et al.

Abstract: Introduction. Shiga toxin-producing Escherichia coli (STEC) belong to a diverse group of gastrointestinal pathogens. The pathogenic potential of STEC is enhanced by the presence of the pathogenicity island called the Locus of Enterocyte Effacement (LEE), including the intimin encoding gene eae. Gap statement. STEC serotypes O128:H2 (Clonal Complex [CC]25), O91:H14 (CC33), and O146:H21 (CC44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In addition to the presence of stx2a , known to be associated with progression to HUS [ 8 ], a review of the sequencing data also identified a plasmid carrying the putative virulence factors, espP , ehxA, saa, ihA and subA . Analysis of UKHSA surveillance data has highlighted that these putative virulence factors have been previously identified in STEC harbouring stx subtypes stx1a, stx1c and stx2b , and causing milder gastrointestinal symptoms than those patients linked to this outbreak [ 41 ]. However, the combined presence of espP , ehxA, saa, ihA and subA with stx2a, may have enhanced the pathogenic potential of this strain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the presence of stx2a , known to be associated with progression to HUS [ 8 ], a review of the sequencing data also identified a plasmid carrying the putative virulence factors, espP , ehxA, saa, ihA and subA . Analysis of UKHSA surveillance data has highlighted that these putative virulence factors have been previously identified in STEC harbouring stx subtypes stx1a, stx1c and stx2b , and causing milder gastrointestinal symptoms than those patients linked to this outbreak [ 41 ]. However, the combined presence of espP , ehxA, saa, ihA and subA with stx2a, may have enhanced the pathogenic potential of this strain.…”
Section: Discussionmentioning
confidence: 99%